An oligosaccharide marker for rapid authentication of edible bird's nest. (30th May 2023) - Li, Li-Feng; Cheng, Hui-Yuan; Lang, Jun; Wong, Tin-Long; Zhang, Ji-Xia; Wu, Wen-Jie; Zhang, Quan-Wei; Kong, Hau-Yee; Lai, Check-Hei; Fung, Hau-Yee; Liu, Man; Bao, Wan-Rong; et al.
Highlights: Rapid authentication of EBN in minutes based on an oligosaccharide was established. The oligosaccharide marker was identified to be Neu5Ac (2–3) Gal by MS and NMR. The marker content could be associated with the quality of EBN products. Abstract: Edible bird's nest (EBN) is a popular and expensive food material. The limited supply and great demand result in the use of adulterants. The authenticity concern is raised due to the lack of appropriate quality markers. Herein, this study aims to provide a specific oligosaccharide marker for rapid EBN authentication. Comparing the benzocaine (ABEE)-labeled saccharide profiles of multiple batches of EBN and adulterants indicates seven unique EBN oligosaccharides. The most abundant one, named BNM001, was selected as a marker and characterized to be Neu5Ac (2–3) Gal by MS and NMR spectra. This new oligosaccharide marker enables a rapid authentication of EBN within 10 min. ABEE labelling of this marker further upgraded the accuracy and sensitivity of the LC-qTOF-MS quantitative analysis. The relative marker content was associated with the quality of EBN products. These results suggest a specific and efficient quality marker for rapid authentication of EBN and related products.